2017
DOI: 10.1128/jcm.00037-17
|View full text |Cite
|
Sign up to set email alerts
|

Dientamoeba fragilis, a Commensal in Children in Danish Day Care Centers

Abstract: Dientamoeba fragilis is an intestinal protozoan of debated clinical significance. Here, we present cross-sectional and longitudinal observations on D. fragilis in children aged 0 to 6 years from a 1-year multi-day-care-center cohort study set in Copenhagen, Denmark. The inclusion period for the cohort was 2009 through 2012. Stool samples collected from the children were accompanied by questionnaires completed by the parents or guardians of the children. Using real-time PCR, D. fragilis was detected in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 16 publications
(23 reference statements)
2
60
0
4
Order By: Relevance
“…Many studies have shown correlation of infection with D. fragilis and clinical symptoms [3,8,9,13,39], while others report no relationship between symptomatic infection and this parasite [44][45][46]. This disparity is not surprising, as manifestations ranging from subclinical to severe gastrointestinal symptoms is typically observed in parasitic enteropathogen infections.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown correlation of infection with D. fragilis and clinical symptoms [3,8,9,13,39], while others report no relationship between symptomatic infection and this parasite [44][45][46]. This disparity is not surprising, as manifestations ranging from subclinical to severe gastrointestinal symptoms is typically observed in parasitic enteropathogen infections.…”
Section: Discussionmentioning
confidence: 99%
“…dispar cysts was positive for E. histolytica with real-time PCR, which underlines the need for typing of these species [14,49,50]. The pathogenic role of D. fragilis has been debated [16][17][18]21,51,52] and the need for screening is questioned. A recent study from Finland also shows that wet mount screening was useful for D. fragilis detection [20].…”
Section: Discussionmentioning
confidence: 99%
“…Dientamoeba fragilis is common, but confirmation of virulence and the potential mechanisms of pathogenicity are yet to be determined [16][17][18][19][20]. Reported prevalence figures vary depending on methods used, patient population and location [20][21][22][23]. Trophozoites of G. intestinalis and E. histolytica are analysed either as motile in fresh samples or by staining of SAF-fixed samples, mainly only on request.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Infection with eukaryotic pathogens often results in acute, moderate-to-severe diarrheal disease and/or chronic malnutrition and stunting, which has 48 significant consequences for morbidity and mortality (3)(4)(5). Conversely, some intestinal 49 parasites are frequently associated with asymptomatic infections, or are even considered 50 commensal (6,7). Giardia, for example, was found in 18 of 1093 (1.6%) of healthy volunteers in 51…”
Section: Importance 23mentioning
confidence: 99%